Pengaruh Informasi Beasiswa dan Status Sosial Terhadap Peminatan Calon Mahasiswa Baru di Universitas Muhadi Setiabudi - Mukson Mukson; Nur Khojin; Maftukhin Maftukhin (JBIMA (Jurnal Bisnis dan Manajemen), 2019)
This study analyzes the effect of scholarship information and social status on the intention of prospective new students at Muhadi Setiabudi University, Brebes. The purpose of this study was to find out and analyze scholarship information and social status towards the intention of prospective new students at Muhadi Setiabudi University. The research method used in this research is quantitative descriptive method. The population and sample of this study were prospective new students of Muhadi Setiabudi University, especially those who registered through the Bidikmisi application, totaling 76 new students. The results showed that the Scholarship Information and Social Status had a positive effect on the intention of prospective new students at Muhadi Setiabudi University, Brebes.